Efficacy of the Rabbit Polyclonal Anti-leptospira Antibody against Homotype or Heterotype Leptospira Infection in Hamster. - Xuemin Jin; Wenlong Zhang; Zhuang Ding; Hai Wang; Dianjun Wu; Xufeng Xie; Tao Lin; Yunhe Fu; Naisheng Zhang; Yongguo Cao (Public Library of Science (PLoS), 2016)
Leptospirosis, caused by Leptospira, is one of the most important of neglected emerging zoonotic diseases that has important impacts on public health worldwide. Polyclonal antibody (pcAb) therapy is a potential method to process a series of pathogens for which there are limited determination of treatment, such as leptospirosis. First, we evaluated the efficacy of pcAb, derived from the sera of rabbits inoculated with Leptospira, against homotype (Leptospira interrogans serovar Lai) or heterotype (Leptospira interrogans serovar Autumnalis) Leptospira infection in a lethal hamster model. The pcAb treatment improved survival compared to the controls. The histopathology's of the infected kidney, liver and lung were also examined by hematoxylin and eosin staining. Using real-time quantitative PCR, we determined that most of the leptospires in the primary organs were almost completely removed by pcAb. In the second experiment, treatments, including antibiotic, pcAb, and combination, were started immediately after occurrence of the first serious sickness mouse in any group. No significant difference in survival rate between pcAb group and antibiotic group was found, but the combination therapy group significantly improved survival rate compared to the others (P<0.05). We conclude that the rabbit pcAb treatment may cure both the homotype and the heterotype lethal Leptospira infections in hamster, and combination therapy improved survival compared to antibiotic group in the late treatment of homotype leptospirosis.